Amyloidosis and inflammatory bowel disease: fact or myth? - Sinagra, Emanuele; Ciofalo, Marco; Tomasello, Giovanni; Cappello, Francesco; Morreale, Gaetano Cristian; Amvrosiadis, Georgios; Damiani, Provvidenza; Damiani, Francesco; Pompei, Giancarlo; Rizzo, Aroldo Gabriele; Canale, Carmelina; Mastrocinque, Giuseppe; et al. (Progress in Nutrition, 2017)
Inflammatory Bowel Disease (IBD), which includes both Crohn’s Disease (CD) and Ulcerative Colitis (UC), is a chronic idiopathic inflammatory disorder affecting the gastrointestinal tract. Extraintestinal manifestations (EIMs) are common in patients with IBD, and occur in 6%-47% of patients with CD or UC. EIMs can involve organs other than the gastrointestinal tract such as skin, eyes, joints, biliary tract, and kidneys. Renal and urinary involvement particularly occurs in 4-23% of patients with IBD. Among the renal complications of IBD, secondary amyloidosis (AA-type, AAA) is a rare but serious complication. Renal amyloidosis has been proven to be the most common lethal manifestation of IBD-associated amyloidosis, since renal involvement rapidly leads to end-stage renal failure. A few studies suggest that AAA is more prevalent in CD than in UC, mainly occurring in male patients with an extensive, long-lasting, and penetrating disease pattern. The therapeutic approaches of IBD-associated AAA are based both on control of the chronic inflammatory process that causes the production and storage of serum amyloid A (SAA), which is a precursor of the amyloid, as well as on destabilizing amyloid fibrils so that they can no longer maintain their β-pleated sheet configuration; however, in patients with end-stage renal disease, the only therapeutic options still available are hemodyalisis and renal transplantation. Whether effective treatment exists for AAA remains controversial.